jungle passports: Fences, mobility, and citizenship at the northeast India-Bangladesh border - Sur, Malini (Philadelphia University of Philadelphia, 2021)
Since the nineteenth century, a succession of states has classified the inhabitants of what are now the borderlands of Northeast India and Bangladesh as Muslim "frontier peasants," "savage mountaineers," and Christian "ethnic minorities," suspecting them to be disloyal subjects, spies, and traitors. In Jungle Passports Malini Sur follows the struggles of these people to secure shifting land, gain access to rice harvests, and smuggle the cattle and garments upon which their livelihoods depend against a background of violence, scarcity, and India's construction of one of the world's longest and most highly militarized border fences.